Pseudomonas aeruginosa PQS mediated virulence regulation and interference - Vico-Oton, Eduard (2019)
Pseudomonas aeruginosa is a ubiquitous bacterium that can be found in most mesophilic aquatic and terrestrial habitats. Furthermore, P. aeruginosa (PA) is an important opportunistic pathogen that can infect humans, animals, insects and plants. P. aeruginosa has three hierarchically organised quorum sensing (QS) systems named las, rhl and pqs. The las and rhl are classic QS systems that use an N-acylhomoserine lactone as autoinducers. The las system is the major QS system of the cell and controls the other two and there is partial redundancy with the rhl system regarding the genes and functions controlled by the system. Activated functions are related to motility, virulence and biofilm formation. The pqs system is a QS system based in alkyl-4(1H)-quinolones (AQs) molecules, specifically the 2-heptyl-3,4-dihydroxyquinoline called pseudomonas quinolone factor (PQS). The pqs system is under control of las and rhl and can in turn influence the expression of rhl. The pqs system controls virulence, iron acquisition, biofilm maturation and the oxidative stress response.